LIVING HADITH AND NAUTICAL DAKWAH: A Contextual Approach to Promoting Environmental Awareness on Kapoposang Island - Tasbih, Tasbih; A. H., Saidah; Bakti, Andi Faisal; Narongrasakhet, Ibrahem (RIWAYAH, 2025)
The study discusses the integration of Living Hadith into nautical da‘wah as an innovative, faith-based approach to enhancing environmental awareness on Kapoposang Island, Indonesia. Employing a qualitative narrative method, data were collected through in-depth interviews, participant observation, and documentation to analyse how prophetic traditions, particularly teachings on cleanliness, are contextualized in environmental stewardship practices. The findings indicate that integrating hadith values into environmental awareness campaigns strengthens community engagement and encourages sustainable behavioural change, especially in waste management and marine conservation. Religious messages, such as the hadith stating that “cleanliness is part of faith,” are translated into concrete actions through community lectures, coastal clean-up activities, and recycling initiatives. The effectiveness of these actions is further reinforced by institutional collaboration between Alauddin State Islamic University Makassar, local government authorities, and community organizations, enabling religious teachings to be implemented in tangible ecological practices. Despite ongoing challenges, including limited human resources, technical capacity, logistical constraints, and external sources of marine pollution, the program has succeeded in fostering a culture of cleanliness rooted in hadith values. Accordingly, this study underscores the potential of nautical da‘wah as a holistic and context-sensitive model of environmental management and recommends its further development and repetitive-comparative studies in other coastal communities across Indonesia. [Penelitian mendiskusikan integrasi living hadis dalam dakwah bahari sebagai pendekatan inovatif berbasis keagamaan untuk meningkatkan kesadaran lingkungan di Pulau Kapoposang, Indonesia. Dengan menggunakan metode kualitatif naratif, data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan dokumentasi untuk menganalisis bagaimana tradisi kenabian, khususnya ajaran tentang kebersihan, dikontekstualisasikan dalam praktik-praktik penjagaan lingkungan. Temuan penelitian menunjukkan bahwa pengintegrasian nilai-nilai hadis ke dalam kampanye peduli lingkungan mampu memperkuat keterlibatan masyarakat, serta mendorong mereka untuk melakukan perubahan perilaku yang berkelanjutan, terutama dalam pengelolaan sampah dan pelestarian lingkungan laut. Pesan-pesan keagamaan, seperti hadis “kebersihan adalah bagian dari iman,” diterjemahkan ke dalam tindakan nyata melalui ceramah komunitas, kegiatan bersih-bersih pesisir, dan inisiatif daur ulang. Efektivitas tindakan tersebut semakin diperkuat dengan adanya kolaborasi kelembagaan antara Universitas Islam Negeri Alauddin Makassar, pemerintah daerah, dan organisasi masyarakat, sehingga ajaran keagamaan dapat diimplementasikan dalam praktik ekologis yang konkret. Meskipun masih menghadapi berbagai tantangan, seperti keterbatasan sumber daya manusia, kapasitas teknis, dan kendala logistik, serta adanya pencemaran laut yang bersumber dari luar wilayah, program ini berhasil menumbuhkan budaya kebersihan yang berakar pada nilai-nilai hadis. Dengan demikian, penelitian ini memberikan kontribusi berupa penegasan potensi dakwah bahari sebagai model pengelolaan lingkungan yang holistik dan kontekstual, serta merekomendasikan pengembangan dan kajian komparatif-repetitif pada komunitas pesisir lainnya di Indonesia.]